Study on impact energy absorption characteristics of biomimetic multi-cell thin-walled structure - CHEN YaTing; HONG YiHao; WU Jun; WU Fei; ZHENG ShiWei; ZHAO ShunQiu (Jixie qiangdu)
Bio-inspired multi-cell thin-walled structure has the advantages of light quality and strong impact resistance. The bio-inspired structures design of lotus root and horsetail were coupled with a thin-walled hollow tube, and two novel bio-inspired multi-cell structures were proposed. One was the coupling structure of thin-walled hollow tube and lotus root (LR-IS) , and the other was the coupling structure of thin-walled hollow tube, lotus root and horsetail (LR-HS-IS) . The models were built by Pro/E and imported into the finite element software Abaqus for numerical simulation analysis. In addition, the 3D printing molding technology was used to make the structures. The mechanical behavior and energy absorption characteristics under axial impact of drop hammer impact test and finite element numerical simulation were studied. The results show that the bio-inspired multi-cell structures have good energy absorption effect, significantly improve the carrying capacity, load efficiency and specific energy absorption. Compared with the individual thin-walled hollow tube, the bio-inspired multi-cell thin-walled structures can not only significantly reduce the impact effect, but also the initial peak force is relatively stable. In addition, the structures are also very consistent with the requirements of lightweight and high energy absorption.